The white matter characteristic of the genu of corpus callosum coupled with pain intensity and negative emotion scores in patients with trigeminal neuralgia: a multivariate analysis - Sun, Baijintao; Zhang, Chuan; Huang, Kai; Bhetuwal, Anup; Yang, Xuezhao; Jing, Chuan; Li, Hongjian; Lu, Hongyu; Zhang, Qingwei; Yang, Hanfeng (Frontiers in Neuroscience, 2024)
Trigeminal neuralgia ( TN ) is a chronic neuropathic pain disorder that not only causes intense pain but also affects the psychological health of patients. Since TN pain intensity and negative emotion may be grounded in our own pain experiences, they exhibit huge inter-individual differences. However, little is known about the relationship among pain intensity, negative emotion, and brain structure in patients with TN. This study investigates the effect of inter-individual differences in pain intensity and negative emotion on brain structure in patients with TN. T1 weighted magnetic resonance imaging and diffusion tensor imaging scans were obtained in 46 patients with TN and 35 healthy controls. All patients with TN underwent pain-related and emotion-related questionnaires. We found a significant difference in the white matter integrity of the patients with TN in comparison with the HC group. It suggested that these white matter regions be involved in pain processing. The most correlation brain region in the partial least squares correlation analysis was the genus of the corpus callosum, which was negatively associated with both pain intensity and negative emotion. Our results suggested that the genu of corpus callosum plays an important role in the cognition of pain perception, the generation and conduction of negative emotions in patients with TN. These findings may deepen our understanding of the pathophysiology of TN.